Serum neutrophil gelatinase-associated lipocalin (NGAL) in patients with Shiga toxin mediated haemolytic uraemic syndrome (STEC-HUS) - Lukasz, Alexander; Beneke, Jan; Menne, Jan; Vetter, Frank; Schmidt, Bernhard M. W.; Schiffer, Mario; Haller, Hermann; Kümpers, Philipp; Kielstein, Jan T. (Thrombosis and Haemostasis, 2014)
Neutrophil gelatinase-associated lipocalin (NGAL) is an increasingly used biomarker for acute kidney injury (AKI). Its utility in adult patients with AKI caused by Shiga toxin producing Escherichia coli infection (STEC)-associated haemolytic-uraemic syndrome (HUS), remains unknown. We aimed to evaluate the prognostic value of serum NGAL admission levels for the need of renal replacement therapy (RRT) in STEC-HUS patients. Baseline serum NGAL was determined by ELISA in 39 patients with STEC O104:H4 infection cared for at Hannover Medical School during the outbreak in Germany through May-July 2011. Patients with HUS had significant higher NGAL levels than healthy controls (379 [248 – 540] vs 39.0 [37.5–45] ng/ml, p < 0.0001). During clinical course, 24 patients required RRT at a median of five days after admission. NGAL admission levels were higher in patients requiring RRT (476 (344–639) ng/ml) compared to patients not requiring RRT (257 (196–426) ng/ml; p < 0.001). Unadjusted and adjusted logistic regression analyses identified NGAL as an independent predictor for need of RRT. In a combined model, a joint NGAL/AKIN classification approach improved the predictive accuracy for need of RRT over either marker alone. The combined categorical cut-off point defined by NGAL ≥ 330 ng/ml and presence of AKI (AKIN ≥ I) on admission correctly identified 20 of 24 patients requiring RRT (odds ratio 20, sensitivity 83%, specificity 80%, negative predictive value 75%, positive predictive value 87%). NGAL may serve as an adjunctive tool to improve risk prediction in patients with STEC-HUS.
Keywords: Neutrophil gelatinase-associated lipocalin; Shiga toxin producing Escherichia coli; haemolytic-uraemic syndrome; acute kidney injury